Influence of implant connections on the expansion of dental implants: systematic review with meta-analysis. - Cunha Melo, Amanda; Silva Canto, Mauro (Brazilian Journal of Implantology and Health Sciences, 2020)
There are different types of implant connections and there is no consensus on the best connection profile for preserving peri-implant bone tissue. Therefore, this systematic review with meta-analysis aimed to analyze the rate of implant loss and level of bone remodeling in implants with different types of connections (Morse taper and external hexagon). The PubMed / Medline, Cochrane Collaboration and SciELO databases were analyzed in order to select the appropriate articles. This review was recorded on the PROSPERO database (CRD42017075429). The data were organized in tables and analyzed qualitatively and quantitatively using the Comprehensive Meta-Analysis Software, being considered as a significant value of p <0.05. The data collected indicated that the failure rate of Morse taper implants (2.6%) was very close to the failure rate of external hexagon implants (3.0%), as well as no significant difference was found in bone loss rates. marginal, when both types of connections were compared, p = 0.556 over an average period of 12 to 60 months. It was concluded that both connections are viable and that more controlled and randomized clinical studies are needed to assess the theme.